Keadilan dalam Akses Pelayanan di Daerah Dalam Perspektif Filsafat Ilmu Berdasarkan Ilmu Hadis - Faisal Wijaya; Abdul Mu'ti; Abdul Kohar; Ropip Ropip; Andi Rosa (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2025)
Fairness in access to public services is one of the important indicators in realizing social welfare. In various regions, especially remote or underdeveloped areas, there is still inequality in access to basic services such as health, education, and government administration. This study aims to examine fairness in access to services in the regions through a philosophy of science approach that includes aspects of ontology, epistemology, and axiology, and is reviewed from the perspective of hadith science. In the perspective of hadith science, many narrations emphasize the importance of leaders being fair to their people, including in the distribution of services. The hadith of the Prophet Muhammad SAW which states that